Prevalence and Associated Factors of Poor Sleep Quality Among Nurses in a Tertiary Care Hospital: A Cross-Sectional Study - Haji Mohamud RY; Mohamed NA; Abdi AA; Osman IM; Ali AN; Doğan S; Mohamud SM; Orhan Z (Risk Management and Healthcare Policy)
Rahma Yusuf Haji Mohamud,1 Nur Adam Mohamed,2 Ali Abdullahi Abdi,3 Iftin Mohamed Osman,4 Amal Nor Ali,5 Serpil Doğan,6 Said Mohamed Mohamud,6 Zerife Orhan7 1Department of Nursing, Mogadishu Somali-Turkiye Recep Tayyip Erdogan Training and Research Hospital, Mogadishu, Somalia; 2Department of Psychiatry and Behavioral Sciences, Mogadishu Somali-Turkiye Recep Tayyip Erdogan Training and Research Hospital, Mogadishu, Somalia; 3Department of Public Health, Benadir Regional Administration and Mogadishu Municipality, Mogadishu, Somalia; 4Department of Education, Mogadishu Somali-Turkiye Recep Tayyip Erdogan Training and Research Hospital, Mogadishu, Somalia; 5Department of Pulmonology, Mogadishu Somali-Turkiye Recep Tayyip Erdogan Training and Research Hospital, Mogadishu, Somalia; 6Department of Medical Microbiology, Mogadishu Somali-Turkiye Recep Tayyip Erdogan Training and Research Hospital, Mogadishu, Somalia; 7Department of Medical Microbiology, Kahramanmaraş Sütçü Imam University, Vocational School of Health Services, Kahramanmaraş, TurkiyeCorrespondence: Rahma Yusuf Haji Mohamud, Department of Nursing, Mogadishu Somali-Turkiye Recep Tayyip Erdogan Training and Research Hospital, Mogadishu, Somalia, Email samiihayusuf@gmail.comBackground: Poor sleep quality among nurses negatively impacts job performance, patient care, and mental well-being, leading to compromised cognitive ability, decision-making, and increased errors, which ultimately jeopardize patient care and safety. This study aimed to determine the prevalence of poor sleep quality and its associated factors among nurses at a tertiary care hospital in Mogadishu, Somalia.Methods: A cross-sectional study was conducted among nurses working at a tertiary care hospital between May and August 2024. Data were collected using a standardized questionnaire, which included socio-demographic information, the Pittsburgh Sleep Quality Index (PSQI), the Depression, Anxiety, and Stress Scale (DASS-21), and the Oslo Social Support Scale (OSSS-3). Bivariate and multivariate logistic regression analyses were used to identify risk factors for poor sleep quality. A p-value of 0.05 was considered the threshold for statistical significance.Results: A total of 280 nurses participated in the study, with 45.7% (95% CI: 39.8– 51.7) reporting poor sleep quality. The odds of reporting poor sleep quality were higher among female nurses (AOR = 2.68; 95% CI: 1.35– 5.32), those working night shifts (AOR = 4.76; 95% CI: 2.06– 11.02), those with poor social support (AOR = 2.82; 95% CI: 1.09– 7.27), and those experiencing depression (AOR = 5.35; 95% CI: 2.22– 12.88), anxiety (AOR = 5.58; 95% CI: 2.61– 11.92), and stress (AOR = 3.92; 95% CI: 1.11– 13.90).Conclusion: This study revealed a significantly high prevalence of poor sleep quality among nurses. These findings underscore the importance of addressing sleep quality as a key component of nursing well-being. It is recommended that nursing managers assess both the mental and physical health of their staff, implement targeted interventions such as stress management and counseling, and develop workplace strategies to improve sleep, including flexible scheduling and education on sleep hygiene.Keywords: poor sleep quality, associated risk factors, nurses, tertiary care hospital, PSQI